Location of Tb(III) ions in hydrated Y zeolites by luminescence spectroscopy - Jeong, Suk Seo; Pyun, C.-H.; Kim, C.-H.; Young, Sun Uh; Wha, Seung Ahn; Suk, Bong Hong (1995)
Luminescence spectroscopy of the Tb3+ ion is used to monitor the variation of the cation distribution in Tb, Na-Y zeolites which were fully rehydrated under ambient conditions after thermal treatments at different temperatures. ？ 1995, Elsevier B.V.